Analyzing the Factors Affecting Case Disposition Efficiency in The Office of Quezon City Prosecutor’s Office - Ablang, Karpov B.; Caina, Jesrah Dian D.; Guardian, Princess E.; Torres, Joseph M.; Malang, Bernandino P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study focused on the Quezon City Prosecutor's Office, aiming to understand the importance of efficient case disposition in the legal system. It used a comprehensive research approach, combining qualitative and quantitative methods to investigate various aspects of the prosecutors' work. The quantitative analysis highlighted the role of caseload volume, case complexity, and time management in case disposition efficiency. However, the qualitative component, based on conversations with prosecutors, provided valuable depth to their recommendations and emphasized the advantages of a centralized system. In conclusion, this research has broader implications beyond Quezon City and serves as a blueprint for legal system reform. It has the potential to enhance the effectiveness, efficiency, and fairness of the justice system, contributing to a safer and more orderly society.